THE ROLE OF STUDENT ACTIVITIES IN DEVELOPING COGNITIVE ACTIVITY AMONG STUDENTS OF THE COLLEGE OF EDUCATION AT MAYSAN UNIVERSITY FROM THE POINT OF VIEW OF UNIVERSITY LECTURERS - Lec. Hayder Abdul Hasan Kareem; Lec. Mazin Abdulaaima Kadimm (Scholars Digest Publishing, 2025)
The objective of this research is to identify the correlation between extracurricular activities and cognitive activity among College of Education students, Misan University, to verify this, the descriptive analytical comparative approach was followed due to its suitability to the research topic. Some tools were also used, which were represented by the scale of extracurricular activities and their relationship to cognitive activity, which was prepared by (the researchers). The study tools were applied to a sample of (100) students from the College of Education students who were randomly selected. The study's findings revealed a beneficial relationship between extracurricular activities and mental activity among College of Education students, and the existence of statistically significant differences between practicing extracurricular activities and non-practicing students in all dimensions. The reality of (mental activity) was also presented, discussed and analyzed. The researchers used the values of arithmetic means and standard deviations for students and identified the differences in the scale of extracurricular activities. Then, the results were presented, analyzed and discussed and a number of conclusions and recommendations were reached, which included: The results showed the highest significant difference in favor of regular students participating in extracurricular activities over other students who do not attend extracurricular activities by obtaining the highest values of arithmetic means and the highest values of standard deviations. The necessity of urging sports coaches and workers in the field of physical education to pay attention to the participation of all college students in sports activities and creating an atmosphere of sports competition.
Keywords: Extracurricular activities, mental activity.